Adaptive Variation Amid High Gene Flow Across a Broad Latitudinal Gradient in the Reef‐Building Honeycomb Worm, Sabellaria alveolata - Edward J. Wilson; Antony M. Knights; Louise B. Firth; Charlotte Corporeau; Amelia Curd; Stanislas F. Dubois; Fernando P. Lima; Rui Seabra; Flavia L. D. Nunes (Molecular Ecology, 2026)
Climate change is already altering, and will continue to reshape, the persistence and spatial structure of marine populations. Understanding metapopulation connectivity and local adaptation is therefore critical for identifying both vulnerable populations and those with adaptive resilience. We applied a seascape genomics approach to investigate connectivity patterns and adaptive responses in the honeycomb worm, Sabellaria alveolata —an intertidal ecosystem engineer that supports high biodiversity and provides essential ecological functions. A total of 286 individuals from 17 sites spanning the entire latitudinal range were genotyped to assess population structure and local adaptation. Outlier analyses (BayeScan and OutFlank) identified six adaptive and 2117 neutral SNPs. Neutral SNP analysis revealed low to moderate genetic differentiation, indicating well‐connected populations. Admixture with possible ancestral gene pools in Southern Edge and Biscay populations suggests the persistence of unique genetic diversity. While connectivity is likely driven by natural larval dispersal, human‐mediated transport resulting from support vessels, aquaculture, marine debris and expanding offshore and coastal infrastructure may also facilitate gene flow, shaping observed genetic patterns. Despite this high connectivity, we detected genetic signatures of adaptation to temperature, salinity and net primary productivity, with adaptive SNPs linked to genes involved in molecular and physiological responses to these environmental factors. Our findings suggest that S. alveolata is likely resilient to climate change and other anthropogenic pressures, making it a valuable model for investigating the genetic and physiological underpinnings of marine population resilience.

Effects of simulated hard and soft release after transport on the stress physiology, metabolic rate and activity levels of juvenile lake sturgeon - Olivia. M. Galloway; Christine. L. Madliger; Britney. L. Firth; Justin. A. Chiotti; Trevor. E. Pitcher (Environmental Biology of Fishes, 2026)

A climate services organization supporting coastal resilience: lessons from the Stone Living Lab - K. A. Dafforn; M. Borrelli; K. Bosma; J. E. K. Byrnes; L. Castro-Diaz; R. F. Chen; J. Christo; D. Cook; F. Peri; R. Shoer; M. Albert; K. Bradley; et al. (Climatic Change, 2026)
There is a growing recognition that effective climate adaptation requires organizations that can translate science into policy-relevant, place-based implementation. The Stone Living Lab (SLL) was established as a climate services organization to help bridge the gap between climate adaptation research and real-world application. In this paper, we present the Lab as a model for how universities and NGOs can partner with government agencies, Indigenous groups, and local communities to strengthen coastal resilience, highlighting the structures, guiding principles and lessons learned over the last five years. Four guiding principles shape and distinguish the Lab’s approach, extending beyond the traditional focus on science and engineering research to also include climate preparedness, education and outreach and policy engagement. These principles continue to evolve in response to experience, particularly in navigating complex partnerships and engaging with stakeholder networks, which require sustained coordination, clear communication, and intentional alignment of roles, expectations, and timelines. Other lessons highlight the importance of visible, place-based solutions, knowledge sharing and maintaining a clear mission focus while balancing short-term outcomes with long-term resilience goals. Our aim here is to provide practical insights for researchers, practitioners and managers seeking to design or strengthen similar climate services organizations.

Habitat enhancement to support invertebrate biodiversity: Comparing gabions to seawalls in an urbanised estuary - J. Seath; L.B. Firth; P.W. Froneman; L. Claassens (Marine Environmental Research, 2026)

Sector expert and public perceptions of greening of grey infrastructure: a case study in Britain’s Ocean City - Jessica R. Allen; Anaëlle J. Lemasson; Melanie J. Bishop; Katherine A. Dafforn; Kate C. Dodds; Mick E. Hanley; Antony M. Knights; Mariana Mayer-Pinto; Abigail McQuatters-Gollop; Maria L. Vozzo; Louise B. Firth (Urban Ecosystems, 2026)

Micro‐Refuges or Ecological Traps: Context‐Dependent Effects of Rock Pools on Intertidal Biodiversity Across Latitudes - Louise B. Firth; Andrea Desiderato; Antony M. Knights; J. David Aguirre; Juan C. Astudillo; Juan C. Azofeifa‐Solano; David T. Bilton; Su Yin Chee; Hartvig C. Christie; Ronaldo A. Christofoletti; Amelia Curd; Katherine A. Dafforn; et al. (Global Ecology and Biogeography, 2026)
Aim We investigated how local‐scale environmental heterogeneity influences biodiversity patterns across broad biogeographic gradients, using intertidal microhabitats as a model system within one of the most environmentally stressful ecosystems on Earth. Location Intertidal habitats at 26 locations (two rocky shore sites per location) across six continents, spanning 98° of latitude (38°S to 60°N). Time Period 2019–2022. Major Taxa Studied Algae, sessile and mobile invertebrates. Methods We compared biodiversity and thermal environments across contrasting microhabitats (rock pools and adjacent emergent rock) along a latitudinal gradient, sampling during environmentally ‘milder’ and ‘harsher’ periods. Biodiversity was quantified using multiple richness metrics (mean, total, unique taxa) and functional diversity. Results Microhabitat differences strongly influenced biodiversity patterns across latitude. Rock pools consistently supported higher taxonomic and functional diversity than emergent rock, irrespective of sampling period, reflecting their ability to buffer thermal extremes, particularly under harsher conditions. Mean species richness exhibited a non‐linear, s‐shaped latitudinal pattern, with lowest values near the equator and higher richness at mid‐latitudes, diverging from classical Latitudinal Diversity Gradient expectations. Biodiversity differences between microhabitats were greatest in temperate regions and diminished at low latitudes, where extreme conditions constrained diversity across habitats. Main Conclusions Local environmental heterogeneity can substantially modify, and in some cases obscure large‐scale biodiversity patterns. By mediating exposure to environmental stress, intertidal microhabitats provide insight into how fine‐scale variability interacts with latitudinal stress gradients to shape biodiversity distributions. Incorporating microhabitat variability into biogeographic frameworks is important for understanding global biodiversity patterns and predicting ecological responses to climate change.

Evaluating the effects of probiotic supplementation and structural enrichment prior to transportation on the stress physiology of reintroduced juvenile Atlantic salmon - D. Roberts; C. L. Madliger; A. I. Mokdad; B. L. Firth; T. E. Pitcher (Environmental Biology of Fishes, 2025)

Effects of fine-scale changes in resource access and social stability on the sociality of foraging flocks of wild birds - Camille A. Troisi; Josh A. Firth; Sam J. Crofts; Gabrielle L. Davidson; Michael S. Reichert; John L. Quinn (Animal Behaviour, 2025)

The use of gabions as an eco-engineering approach to enhance estuarine fish habitats in urbanised waterways - J.L. Seath; L.B. Firth; P.W. Froneman; L. Claassens (Ecological Engineering, 2025)

Oxygen consumption rate during recovery from loss of equilibrium induced by warming, hypoxia, or exhaustive exercise in rainbow darter ( Etheostoma caeruleum ) - Brittney G. Borowiec; Britney L. Firth; Paul M. Craig (Journal of Fish Biology, 2024)
Animals routinely encounter environmental (e.g., high temperatures and hypoxia) as well as physiological perturbations (e.g., exercise and digestion) that may threaten homeostasis. However, comparing the relative threat or “disruptiveness” imposed by different stressors is difficult, as stressors vary in their mechanisms, effects, and timescales. We exploited the fact that several acute stressors can induce the loss of equilibrium (LOE) in fish to (i) compare the metabolic recovery profiles of three environmentally relevant stressors and (ii) test the concept that LOE could be used as a physiological calibration for the intensity of different stressors. We focused on Etheostoma caeruleum , a species that routinely copes with environmental fluctuations in temperature and oxygen and that relies on burst swimming to relocate and avoid predators, as our model. Using stop‐flow (intermittent) respirometry, we tracked the oxygen consumption rate (MO 2 ) as E. caeruleum recovered from LOE induced by hypoxia (PO 2 at LOE), warming (critical thermal maximum, CT max ), or exhaustive exercise. Regardless of the stressor used, E. caeruleum recovered rapidly, returning to routine MO 2 within ~3 h. Fish recovering from hypoxia and warming had similar maximum MO 2 , aerobic scopes, recovery time, and total excess post‐hypoxia or post‐warming oxygen consumption. Though exhaustive exercise induced a greater maximum MO 2 and corresponding higher aerobic scope than warming or hypoxia, its recovery profile was otherwise similar to the other stressors, suggesting that “calibration” to a physiological state such as LOE may be a viable conceptual approach for investigators interested in questions related to multiple stressors, cross tolerance, and how animals cope with challenges to homeostasis.

Impact of turbidity on the gill morphology and hypoxia tolerance of eastern sand darter ( Ammocrypta pellucida ) - Britney L. Firth; Paul M. Craig; D. Andrew R. Drake; Michael Power (Journal of Fish Biology, 2024)
Anthropogenic stressors such as agriculture and urbanization can increase river turbidity, which can negatively impact fish gill morphology and growth due to reduced oxygen in the benthic environment. We assessed the gill morphology, field metabolic rate (FMR), and two hypoxia tolerance metrics (oxygen partial pressure at loss of equilibrium, PO 2 at LOE, and critical oxygen tension, P crit ) of eastern sand darter ( Ammocrypta pellucida ), a small benthic fish listed as threatened under the Species at Risk Act in Canada, from rivers in southern Ontario. Field trials were conducted streamside in the Grand River (August 2019; mean NTU 8) and in the comparatively more turbid Thames River (August 2020; mean NTU 94) to test the effect of turbidity on each physiological endpoint. Gills were collected from incidental mortalities and museum specimens, and were assessed using hematoxylin and eosin and immunofluorescent staining. The between‐river comparison indicated that turbidity significantly increased interlamellar space and filament width but had no significant influence on other gill morphometrics or FMR. Turbidity significantly increased PO 2 at LOE (i.e., fish had a lower hypoxia tolerance) but did not significantly impact P crit . Therefore, although turbidity influences hypoxia tolerance through LOE, turbidity levels were not sufficiently high in the study rivers to contribute to measurable changes in gill morphology or metabolism in the wild. Determining whether changes in gill morphology or metabolism occur under higherturbidity levels would help resolve the ecological importance of turbidity on species physiology in urban and agricultural ecosystems.

Taking sides? Aspect has limited influence on soil environment or litter decomposition in pan-European study of roadside verges - A. Amstutz; LB. Firth; JI. Spicer; P. De Frenne; L. Gómez-Aparicio; BJ. Graae; S. Kuś; S. Lindmo; A. Orczewska; F. Rodríguez-Sánchez; P. Vangansbeke; T. Vanneste; et al. (Pedobiologia, 2024)

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

Classification of new morbillivirus and jeilongvirus sequences from bats sampled in Brazil and Malaysia - Heather L. Wells; Elizabeth Loh; Alessandra Nava; Mónica Romero Solorio; Mei Ho Lee; Jimmy Lee; Jum R. A. Sukor; Isamara Navarrete-Macias; Eliza Liang; Cadhla Firth; Jonathan H. Epstein; Melinda K. Rostal; et al. (Archives of Virology, 2022)
As part of a broad One Health surveillance effort to detect novel viruses in wildlife and people, we report several paramyxovirus sequences sampled primarily from bats during 2013 and 2014 in Brazil and Malaysia, including seven from which we recovered full-length genomes. Of these, six represent the first full-length paramyxovirid genomes sequenced from the Americas, including two that are the first full-length bat morbillivirus genome sequences published to date. Our findings add to the vast number of viral sequences in public repositories, which have been increasing considerably in recent years due to the rising accessibility of metagenomics. Taxonomic classification of these sequences in the absence of phenotypic data has been a significant challenge, particularly in the subfamily Orthoparamyxovirinae , where the rate of discovery of novel sequences has been substantial. Using pairwise amino acid sequence classification (PAASC), we propose that five of these sequences belong to members of the genus Jeilongvirus and two belong to members of the genus Morbillivirus . We also highlight inconsistencies in the classification of Tupaia virus and Mòjiāng virus using the same demarcation criteria and suggest reclassification of these viruses into new genera. Importantly, this study underscores the critical importance of sequence length in PAASC analysis as well as the importance of biological characteristics such as genome organization in the taxonomic classification of viral sequences.

Nitrogen removal in constructed marshes at sites protected from and exposed to waves - Nigel A. Temple; Eric L. Sparks; Just Cebrian; Sara E. Martin; Daniel C. Firth (Wetlands Ecology and Management, 2021)

Subzero, saline incubations of Colwellia psychrerythraea reveal strategies and biomarkers for sustained life in extreme icy environments - Miranda C. Mudge; Brook L. Nunn; Erin Firth; Marcela Ewert; Kianna Hales; William E. Fondrie; William S. Noble; Jonathan Toner; Bonnie Light; Karen A. Junge (Environmental Microbiology, 2021)
Summary Colwellia psychrerythraea is a marine psychrophilic bacterium known for its remarkable ability to maintain activity during long‐term exposure to extreme subzero temperatures and correspondingly high salinities in sea ice. These microorganisms must have adaptations to both high salinity and low temperature to survive, be metabolically active, or grow in the ice. Here, we report on an experimental design that allowed us to monitor culturability, cell abundance, activity and proteomic signatures of C. psychrerythraea strain 34H ( Cp 34H) in subzero brines and supercooled sea water through long‐term incubations under eight conditions with varying subzero temperatures, salinities and nutrient additions. Shotgun proteomics found novel metabolic strategies used to maintain culturability in response to each independent experimental variable, particularly in pathways regulating carbon, nitrogen and fatty acid metabolism. Statistical analysis of abundances of proteins uniquely identified in isolated conditions provide metabolism‐specific protein biosignatures indicative of growth or survival in either increased salinity, decreased temperature, or nutrient limitation. Additionally, to aid in the search for extant life on other icy worlds, analysis of detected short peptides in −10°C incubations after 4 months identified over 500 potential biosignatures that could indicate the presence of terrestrial‐like cold‐active or halophilic metabolisms on other icy worlds.

Musical Chairs on Temperate Reefs: Species Turnover and Replacement Within Functional Groups Explain Regional Diversity Variation in Assemblages Associated With Honeycomb Worms - Alexandre Muller; Camille Poitrimol; Flávia L. D. Nunes; Aurélien Boyé; Amelia Curd; Nicolas Desroy; Louise B. Firth; Laura Bush; Andrew J. Davies; Fernando P. Lima; Martin P. Marzloff; Claudia Meneghesso; et al. (Frontiers in Marine Science, 2021)
Reef-building species are recognized as having an important ecological role and as generally enhancing the diversity of benthic organisms in marine habitats. However, although these ecosystem engineers have a facilitating role for some species, they may exclude or compete with others. The honeycomb worm Sabellaria alveolata ( Linnaeus, 1767 ) is an important foundation species, commonly found from northwest Ireland to northern Mauritania, whose reef structures increase the physical complexity of the marine benthos, supporting high levels of biodiversity. Local patterns and regional differences in taxonomic and functional diversity were examined in honeycomb worm reefs from 10 sites along the northeastern Atlantic to explore variation in diversity across biogeographic regions and the potential effects of environmental drivers. While taxonomic composition varied across the study sites, levels of diversity remained relatively constant along the European coast. Assemblages showed high levels of species turnover compared to differences in richness, which varied primarily in response to sea surface temperatures and sediment content, the latter suggesting that local characteristics of the reef had a greater effect on community composition than the density of the engineering species. In contrast, the functional composition of assemblages was similar regardless of taxonomic composition or biogeography, with five functional groups being observed in all sites and only small differences in abundance in these groups being detected. Functional groups represented primarily filter-feeders and deposit-feeders, with the notable absence of herbivores, indicating that the reefs may act as biological filters for some species from the local pool of organisms. Redundancy was observed within functional groups that may indicate that honeycomb worm reefs can offer similar niche properties to its associated assemblages across varying environmental conditions. These results highlight the advantages of comparing taxonomic and functional metrics, which allow identification of a number of ecological processes that structure marine communities.

Diet overlap of common and at-risk riverine benthic fishes before and after Round Goby (Neogobius melanostomus) invasion - B. L. Firth; M. S. Poesch; M. A. Koops; D. A. R. Drake; M. Power (Biological Invasions, 2021)

A global analysis of complexity–biodiversity relationships on marine artificial structures - Elisabeth M. A. Strain; Peter D. Steinberg; Maria Vozzo; Emma L. Johnston; Marco Abbiati; Moises A. Aguilera; Laura Airoldi; J. David Aguirre; Gail Ashton; Maritina Bernardi; Paul Brooks; Benny K. K. Chan; et al. (Global Ecology and Biogeography, 2021)
Aim Topographic complexity is widely accepted as a key driver of biodiversity, but at the patch‐scale, complexity–biodiversity relationships may vary spatially and temporally according to the environmental stressors complexity mitigates, and the species richness and identity of potential colonists. Using a manipulative experiment, we assessed spatial variation in patch‐scale effects of complexity on intertidal biodiversity. Location 27 sites within 14 estuaries/bays distributed globally. Time period 2015–2017. Major taxa studied Functional groups of algae, sessile and mobile invertebrates. Methods Concrete tiles of differing complexity (flat; 2.5‐cm or 5‐cm complex) were affixed at low–high intertidal elevation on coastal defence structures, and the richness and abundance of the colonizing taxa were quantified after 12 months. Results The patch‐scale effects of complexity varied spatially and among functional groups. Complexity had neutral to positive effects on total, invertebrate and algal taxa richness, and invertebrate abundances. However, effects on the abundance of algae ranged from positive to negative, depending on location and functional group. The tidal elevation at which tiles were placed accounted for some variation. The total and invertebrate richness were greater at low or mid than at high intertidal elevations. Latitude was also an important source of spatial variation, with the effects of complexity on total richness and mobile mollusc abundance greatest at lower latitudes, whilst the cover of sessile invertebrates and sessile molluscs responded most strongly to complexity at higher latitudes. Conclusions After 12 months, patch‐scale relationships between biodiversity and habitat complexity were not universally positive. Instead, the relationship varied among functional groups and according to local abiotic and biotic conditions. This result challenges the assumption that effects of complexity on biodiversity are universally positive. The variable effect of complexity has ramifications for community and applied ecology, including eco‐engineering and restoration that seek to bolster biodiversity through the addition of complexity.

Discovery of a novel Tymoviridae-like virus in mosquitoes from Mexico - Jermilia Charles; Chandra S. Tangudu; Stefanie L. Hurt; Charlotte Tumescheit; Andrew E. Firth; Julian E. Garcia-Rejon; Carlos Machain-Williams; Bradley J. Blitvich (Archives of Virology, 2019)

A barnavirus sequence mined from a transcriptome of the Antarctic pearlwort Colobanthus quitensis - Max L. Nibert; Austin R. Manny; Humberto J. Debat; Andrew E. Firth; Laura Bertini; Carla Caruso (Archives of Virology, 2018)

Inhibition of the Voltage-Dependent K+ Current by the Tricyclic Antidepressant Desipramine in Rabbit Coronary Arterial Smooth Muscle Cells - Sung Eun Shin; Hongliang Li; Jin Ryeol An; Mi Seon Seo; Sung Hun Na; Won-Kyo Jung; Amy L. Firth; Kwon-Soo Ha; Eun-Taek Han; Seok-Ho Hong; Il-Whan Choi; Won Sun Park (Cardiovascular Toxicology, 2018)

Selective serotonin reuptake inhibitor sertraline inhibits voltage-dependent K+ channels in rabbit coronary arterial smooth muscle cells - Han Sol Kim; Hongliang Li; Hye Won Kim; Sung Eun Shin; Il-Whan Choi; Amy L Firth; Hyoweon Bang; Young Min Bae; Won Sun Park (Journal of Biosciences, 2016)

The class III anti-arrhythmic agent, amiodarone, inhibits voltage-dependent K+ channels in rabbit coronary arterial smooth muscle cells - Hongliang Li; Han Sol Kim; Hye Won Kim; Sung Eun Shin; Won-Kyo Jung; Kwon-Soo Ha; Eun-Taek Han; Seok-Ho Hong; Amy L. Firth; Young Min Bae; Il-Whan Choi; Won Sun Park (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Side-effects of protein kinase inhibitors on ion channels - Youn Kyoung Son; Hongzoo Park; Amy L Firth; Won Sun Park (Journal of Biosciences, 2013)

Novel one-stop multidisciplinary follow-up clinic significantly improves cancer risk management in BRCA1/2 carriers - G. Pichert; C. Jacobs; I. Jacobs; U. Menon; R. Manchanda; M. Johnson; H. Hamed; C. Firth; M. Evison; A. Tutt; L. de Silva; C. Langman; et al. (Familial Cancer, 2010)

Effect of caffeine ingestion on one-repetition maximum muscular strength - Todd A. Astorino; Riana L. Rohmann; Kelli Firth (European Journal of Applied Physiology, 2007)